Skeletal muscle regeneration in zebrafish - Pipalia, TG; Sultan, SHA; Koth, J; Knight, RD; Hughes, SM (Springer, 2023)
Muscle regeneration models have revealed mechanisms of inflammation, wound clearance, and stem cell-directed repair of damage, thereby informing therapy. Whereas studies of muscle repair are most advanced in rodents, the zebrafish is emerging as an additional model organism with genetic and optical advantages. Various muscle wounding protocols (both chemical and physical) have been published. Here we describe simple, cheap, precise, adaptable, and effective wounding protocols and analysis methods for two stages of a larval zebrafish skeletal muscle regeneration model. We show examples of how muscle damage, ingression of muscle stem cells, immune cells, and regeneration of fibers can be monitored over an extended timecourse in individual larvae. Such analyses have the potential to greatly enhance understanding, by reducing the need to average regeneration responses across individuals subjected to an unavoidably variable wound stimulus.